Asuhan Keperawatan Gangguan Integritas Kulit/Jaringan pada Diabetes Mellitus Tipe 2: Nursing Care for Skin/Tissue Integrity Disorders in Type 2 Diabetes Mellitus - Rohmah Dina Nur Kusuma; Sebayang, Septian Mixrova; Wibowo, Tophan Heri (Journal of Nursing Education and Practice, 2023)
Background: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to insulin secretion, or both. The disorder causes abnormalities in the metabolism of carbohydrates, fats, and proteins. Purpose: To describe nursing care for skin/tissue integrity disorders in Mr. S with type II diabetes mellitus in the Ar Rahman room RSI Purwokerto. Method: Descriptive research design in the form of a case study with a nursing process approach consisting of assessment, nursing diagnosis, intervention, implementation, and evaluation. Nursing care was carried out to Mr. S for 3x24 hours. Data collection techniques using observation, interviews, physical examination, and documentation. Results: The nursing evaluation which was carried out on June 16-18 2022 was carried out using the SOAP method, including subjectively the patient stating that his body was still weak, the wound had not healed and the pain had decreased. Objective, K/u: weak, GDS: 320mg/dl, a wound with a length of 3 cm and a width of 2 cm is visible, on the dressing there is seepage of liquid reddish yellow smelling and festering, the patient can tilt right and left, the total score of the BJWAT assessment increases from 28 to 29. Analysis, the problem not resolved, continue the intervention. Conclusion: Evaluation on the third day of tissue damage, skin damage, pain and redness has not been resolved.